Incorporation of 2D nanomaterial - Graphene Oxide (GO) in fibre reinforced cementitious composites: impact on hydration, mechanical and microstructure characteristics - Raj Samraj; Rama Mohan Rao Pannem (Nano Express)
In this current study, graphene oxide (GO) was incorporated to the fibre reinforced concrete (FRC), to investigate the synergetic effect on physical, mechanical and microstructural properties. A comprehensive investigation was made with both cement mortar and concrete with distinct mixes incorporating varying dosages of GOup to 0.08%, SF (micro-steel fibre) up to 0.8% and selecting the ideal dosage from the preliminary test for GO+SF combination in cementitious composite. Non-destructive test of ultrasonic pulse velocity (UPV) is carried out after standard curing time. Compressive and split tensile strength were carried out for the samples cured up to 28 days and showed a significant enhancement of strength with inclusion of both GO and SF. The ideal dosage for the combination of GO+SF (0.06% + 0.5%) is confirmed to assess the synergistic effect, the findings exhibited an enhanced compressive strength by 59.4%. The UPV values of the different mixes stating the quality and homogeneity of matrix are well correlated with the compressive strength results, Thus, confirming the reliability of UPV test on evaluating the mechanical performance of concrete. The internal microstructure and morphology of the composite has been scrutinized by advanced techniques of FE-SEM and Micro-CT scan, resulted in observing the matrix and finding out the increased hydration, enhanced denser products and reduced porosity. The results facilitated an in-depth understanding of the impact of nano-microfibre in cementitious composites as well as an intriguing nano-micro material which could meet the evolving needs of building materials utilized in construction industry.